2013
DOI: 10.1179/1743281213y.0000000145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B2O3on phase compositions of high Ti bearing titanomagnetite sinter

Abstract: The phase compositions of high Ti bearing titanomagnetite sinter with different contents of B 2 O 3 were studied at 1623 K under an oxygen partial pressure of 5610 23 atm. The results showed that B 2 O 3 mainly gathered in Ca 2 SiO 4 phase and formed 2CaO.xSiO 2 .2/3(12x)(B 2 O 3 ) phase. The appearance of B 2 O 3 can restrain the precipitation of CaTiO 3 and 2CaO.xSiO 2 .2/3(12x)(B 2 O 3 ) and promote the amount of Fe bearing mineral phase in the current experimental condition. In addition, the shape of CaTiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ren et al [16,17] researched the influencing pattern of different B 2 O 3 contents on the mineral phase of high-titanium-type VTM and the qualities of sinter; they pronounced that B 2 O 3 was mainly deposited in the 2CaO In summary, we find that adding boron slime, boric acid, and boron-iron concentrate could improve the strength and the metallurgical performance of sinter and reduce the lowtemperature pulverulent ratio, which is conducive to the blast furnace. It is not difficult to find that boron oxide plays a very important role in the sintering process.…”
Section: Introductionmentioning
confidence: 59%
“…Ren et al [16,17] researched the influencing pattern of different B 2 O 3 contents on the mineral phase of high-titanium-type VTM and the qualities of sinter; they pronounced that B 2 O 3 was mainly deposited in the 2CaO In summary, we find that adding boron slime, boric acid, and boron-iron concentrate could improve the strength and the metallurgical performance of sinter and reduce the lowtemperature pulverulent ratio, which is conducive to the blast furnace. It is not difficult to find that boron oxide plays a very important role in the sintering process.…”
Section: Introductionmentioning
confidence: 59%
“…Thus, a small quantity of modifier which could make Ti element enriched in the anosovite crystal is desired. In our previous studies, the addition of appropriate amount of B 2 O 3 not only enhances the metallurgical properties of high Tibearing titanomagnetite sinter, 24,25 but decreases the viscosity of high Ti-bearing blast furnace slag to improve its fluidity. 26 Particularly, 2.5% B 2 O 3 was added into high Ti-bearing blast furnace slag and the precipitation kinetics of anosovite crystal in the modified slag in our previous study.…”
Section: Introductionmentioning
confidence: 97%
“…In our previous research [9][10][11][12][13][14][15][16], Ti-bearing ore sintering and Ti-bearing slag characteristics were studied systematically. B 2 O 3 was chosen as the modifier for obtaining the Ti-rich phases, and the results showed that the rise of the (Mg + Al)/(Ca + Si) ratio and B 2 O 3 in slag were beneficial to form [TiO 6 ] 8− octahedral units and thus beneficial to the precipitation of anosovite from the TBBF slag [14,15].…”
Section: Introductionmentioning
confidence: 99%